An environmentally friendly high-dosage RAP recycled cement stabilized gravel mixture and preparation method thereof

Through the combination of high-addition RAP, new aggregates and health-free agents, combined with the joint stirring method, the variability parameters of RAP materials are limited, and the problems of different performance and uneven quality of RAP materials are solved, and the strength performance of water-stable mixtures and the improvement of material utilization efficiency are achieved.

CN118771805BActive Publication Date: 2025-03-18NANJING PUBLIC PROJECT CONSTRUCTION CENTER +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410987083.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-23
Publication Date
2025-03-18
Estimated Expiration
2044-07-23

Smart Images

  • Figure CN118771805B_ABST
    Figure CN118771805B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of cement-stabilized crushed stone mixture preparation, and specifically relates to an environmentally friendly high-dosage RAP recycled cement-stabilized crushed stone mixture and a preparation method thereof, wherein the high-dosage RAP water-stabilized mixture comprises graded crushed stone, cement and a curing agent; the graded crushed stone is composed of the following materials by mass percentage: 12% to 20% RAP1 # Material, 18%~20%RAP2 # Material, 10%RAP3 # The raw material is 32% to 42% coarse aggregate and 18% fine aggregate; the cement addition accounts for 2.5% to 4% of the total weight of the high-dosage RAP recycled water-stabilized mixture; the amount of curing agent added is 6% to 8% of the cement mass. Through the co-mixing method, the various parameters of the recycled RAP material are limited, the use range of RAP material can be standardized, and the mechanical properties of the high-dosage RAP water-stabilized mixture are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cement-stabilized crushed stone mixture preparation, and specifically relates to an environmentally friendly high-dosage RAP recycled cement-stabilized crushed stone mixture and a preparation method thereof. Background Art

[0002] With the rapid development of highway transportation in my country, national and provincial trunk highway networks have gradually taken shape, the proportion of newly built highways has decreased year by year, and the proportion of reconstruction and overhaul projects has continued to expand. If the asphalt pavement reconstruction continues to use traditional methods, a large amount of asphalt mixtures from excavation and milling will be discarded, increasing the asphalt and gravel materials required for reconstructing the road surface, which not only pollutes the environment but also wastes resources.

[0003] In order to solve the problem of waste of asphalt milling materials and environmental pollution, recycled asphalt mixture (RAP) technology has been widely used in road surface layers. With the increase in renovation and expansion projects, the total amount of RAP continues to increase. The application of RAP in the surface layer alone can no longer meet the needs of recycled asphalt mixture processing. The application of RAP in cement-stabilized crushed stone with an appropriate amount of waste asphalt mixture can not only improve the various road performance of the road base, but also improve its fatigue performance, antifreeze performance and scouring performance.

[0004] In the prior art, for example, a Chinese patent with publication number CN113698138A provides a RAP high-dosage recycled mixture and a preparation method thereof, which uses rubber powder to perform TB modification on the base asphalt and adds nano sodium carbonate, thereby avoiding the disadvantages of traditional rubber asphalt such as high viscosity, poor thermal storage stability, and easy segregation, and improving the water stability of RAP. Another example is a Chinese patent with publication number CN116693242B, which provides a preparation method for cold recycled asphalt mixture, cold recycled asphalt mixture and application, which improves the bonding force between RAP and other components in the cold recycled asphalt mixture by adding admixtures and emulsified asphalt during the production process of the emulsified asphalt recycled mixture, and further improves the splitting strength, freeze-thaw splitting strength ratio and dynamic stability of the road surface to which it is applied.

[0005] However, the above-mentioned prior art still has the following problems: the performance of the RAP material currently used has declined to a certain extent due to the influence of various loads on the original road surface, and due to the lack of a unified milling method, the recycled RAP material has different properties and uneven quality, resulting in a decrease in the strength performance of the road base using the RAP material, which has caused great trouble to the design process of the recycling of RAP materials. Summary of the invention

[0006] In view of the above-mentioned problems of inconsistent performance and uneven quality of current RAP materials, the present invention provides an environmentally friendly high-dosage RAP recycled cement-stabilized crushed stone mixture and a preparation method thereof, using high-dosage RAP, new aggregate and curing agent-free as materials, and through a co-mixing method, limiting the variability parameters of the recycled RAP materials, which can standardize the use of RAP materials, stably improve the strength performance of high-dosage RAP water-stabilized mixture, and make it meet the use standards of the pavement base. The specific technical scheme is as follows:

[0007] First, the present invention provides an environmentally friendly high-dosage RAP recycled cement stabilized gravel mixture, an environmentally friendly high-dosage RAP recycled cement stabilized gravel mixture, comprising graded gravel, cement and a curing agent; the graded gravel is composed of the following parts by weight: 12% to 20% RAP1 # Material, 18%~20%RAP2 # Material, 10%RAP3 # material, 32% to 42% coarse aggregate, and 18% fine aggregate; the cement addition amount is 2.5% to 4% of the high-dosage RAP recycled water-stabilized mixture; the curing agent addition amount is 6% to 8% of the cement addition amount.

[0008] Furthermore, the moisture content of the high-dosage RAP recycled water-stabilized mixture is 4.0% to 4.5%; the maximum dry density is 2.200

[0009] g / cm 3 ~2.221 g / cm 3 .

[0010] Furthermore, the RAP1 # Particle size is 10mm~20mm, RAP2 # Particle size is 5mm~10mm, RAP3 # The particle size is greater than 0mm and less than 5mm, the coarse aggregate particle size is 16mm~31.5mm, and the fine aggregate particle size is greater than 0mm and less than 2.36mm.

[0011] Furthermore, the RAP1 # Material, RAP2 # Materials and RAP3 # The coefficient of variation of the asphalt content in the old material is 4.5%~5.5%; the coefficient of variation of the needle penetration is 6.5%~7.5%; the coefficient of variation of the softening point is 5%~5.5%; and the coefficient of variation of the elongation at 10℃ is 6%~9.5%.

[0012] Furthermore, the curing agent includes an anionic surfactant and a swelling agent, wherein the anionic surfactant includes any one or more of anionic polyacrylamide and fatty alcohol polyoxyethylene ether phosphate, and the swelling agent includes any one or more of calcium magnesium oxide swelling agents and calcium sulfoaluminate swelling agents; the curing agent meets the following technical indicators: pH value is 7 to 9; alkali content is ≤0.75%; specific surface area is ≥200m 2 / kg; initial setting time ≥3h, final setting time ≤10h; water reduction rate ≥25%.

[0013] The present invention also provides a method for preparing an environmentally friendly high-dosage RAP recycled cement stabilized gravel mixture, comprising the following steps:

[0014] Step 1: RAP material recovery and screening: Select the old road surface to be milled to obtain the recovered materials, crush and screen the recovered materials into multiple grades of RAP materials, and store them for future use after testing their variability;

[0015] Step 2: Mixing the mixture: Mix the qualified RAP material with coarse aggregate and fine aggregate to obtain a mixture. After the mixture is sieved to test whether its gradation range is qualified, cement and curing agent are added to the mixture in sequence, and stirred to make a high-dosage RAP water-stabilized mixture with rapid curing.

[0016] Furthermore, in the step 1, the milling depth of the old road surface is 30 cm to 40 cm; the milling speed is 10 m / min to 15 m / min.

[0017] Furthermore, the gradation range of the mixture in step 2 meets the following requirements:

[0018]

[0019] Furthermore, in step 2, the health-preserving agent is pre-dissolved in water.

[0020] Compared with the prior art, the grouting material of the present invention has the following beneficial effects:

[0021] 1) The invention adopts a high amount of RAP material in the mixture, which can consume more RAP material, save production costs and solve the problem of RAP material recycling. At the same time, the invention aims at the problem that the quality of the recycled RAP material is uneven and the performance is highly volatile due to the different initial gradations of different pavement structure layers, different asphalt content and properties, and the inconsistent external environment during the use process, which causes the strength performance of the pavement base using RAP material to decrease and the design and use process of RAP material to be difficult. After recycling RAP, the inventor introduced a coefficient of variation to evaluate RAP material, and put forward requirements for the variability of the recycled RAP material. By crushing and screening, the recycled RAP material is ensured to meet the use standard, the quality stability and uniformity of the RAP material is guaranteed, the difficulty of designing and using RAP is reduced, and the strength of the pavement base using RAP material is improved. At the same time, by limiting the variability of RAP material, the mixture can reach the gradation range of use, which can further save the amount of cement used and improve the comprehensive mechanical properties of the base prepared by the water-stabilized mixture of the invention.

[0022] 2) The present invention screens the RAP material carefully and divides the RAP material into three particle sizes. In use, the addition amount of the RAP material of the three particle sizes is divided in detail, and the corresponding amount of new aggregate is used in combination. Under the condition of ensuring a high addition amount of RAP, the splitting strength, compressive rebound modulus, fatigue resistance and anti-scouring performance of the water-stable base are effectively improved, so that it can not only be used as a base material, but also as an upper base material, which broadens the scope of application research. At the same time, the use of a curing agent can produce a synergistic effect, quickly improve the unconfined compressive strength of the water-stable base within 7 days of age, and reduce the maintenance period of the water-stable base.

[0023] 3) The present invention adds a curing agent to the water-stabilized mixture. The curing agent contains anionic surfactant. After the curing agent is added to the cement-stabilized gravel mixture, it is adsorbed on the surface of the cement material particles. The particles will have the same charge and be evenly dispersed, which improves the construction and workability of the mixture. At the same time, due to the formation of an adsorption film on the surface of the particles, the growth of cement crystals is more perfect, the network structure is more dense, the strength and density of the matrix are improved, and the rapid increase in the strength of the cement-stabilized gravel mixture is achieved in a short period of time. In addition, the curing agent contains a micro-expansion component to resist the shrinkage of the matrix.

[0024] 4) Compared with the prior art, the present invention accurately limits the amount of cement added to the water-stabilized mixture and the amount of curing agent added in conjunction with the amount of RAP used, and finds that too much or too little curing agent added will affect the unconfined compressive strength of the water-stabilized base and the use effect of the water-stabilized mixture. At the same time, after using RAP materials at high dosages, too much or too little cement added will also have a significant effect on the unconfined compressive strength of the mixture. The present invention explores the optimal use range of cement addition and curing agent addition, improves the utilization efficiency of materials, saves the cost of raw materials, and ensures the compressive performance of the water-stabilized mixture. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a core sample at the age of 1 day prepared from an environmentally friendly high-dosage RAP recycled cement stabilized gravel mixture in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the present invention more clear, the technical solution of the present invention will be clearly and completely described below in conjunction with embodiments.

[0027] Example 1

[0028] This embodiment provides a method for preparing an environmentally friendly high-dosage RAP recycled cement stabilized gravel mixture, which specifically includes the following steps:

[0029] Step 1: RAP material recovery and screening: Select the old road surface to be milled to obtain the recovered materials, crush and screen the recovered materials into multiple grades of RAP materials, and store them for future use after testing their variability;

[0030] Specifically, firstly, after fully investigating the condition of the old road surface, collecting the original data of the old road surface and the repair and maintenance records, the different road sections are milled in sections. The maximum milling width during milling should be no less than 2m, and the milling depth should be able to meet the layered milling thickness requirements. The milling depth should be between 30cm and 40cm, and the cutter head spacing should be no more than 18mm, with a number of no less than 160. At the same time, the milling speed needs to be controlled between 10m / min and 15m / min, such as 12m / min.

[0031] After milling, RAP of different sources, varieties and specifications shall be separated for pre-treatment such as crushing and screening. RAP with a particle size exceeding 26.5 mm and agglomerated RAP shall be crushed by a crusher.

[0032] All RAP materials are divided into at least three grades. In this embodiment, the RAP materials are screened into three grades according to the particle size, namely RAP1 # Material, RAP2 # material, RAP3 #Calculate RAP1 based on the screening results # Material, RAP2 # material, RAP3 # The coefficient of variation of the material is calculated as follows:

[0033]

[0034] In the formula CV represents the coefficient of variation, S represents the standard deviation, Represents the mean.

[0035] In this example, RAP1 # The coefficients of variation of the passing rate of the 19mm and 9.5mm sieves are 2.10% and 6.03% respectively; the coefficients of variation of the passing rate of the 4.75mm sieve are 11.10%. # The coefficient of variation of the passing rate of the material with a 9.5 mm sieve hole is 3.45%; the coefficients of variation of the passing rate of the material with a 4.75 mm sieve hole and a 2.36 mm sieve hole are 11.52% and 13.24% respectively. # The coefficients of variation of the passing rates of materials with 4.75mm and 0.075mm sieve apertures are 4.55% and 9.93%, respectively.

[0036] The coefficient of variation of the recycled asphalt in RAP in this embodiment is shown in Table 1:

[0037]

[0038] Step 2: Mixing the mixture: Mix the qualified RAP material with coarse aggregate and fine aggregate to obtain a mixture, then add cement and curing agent to the mixture in sequence, stir and mix to form a high-dosage RAP water-stabilized mixture with rapid curing.

[0039] Specifically, the qualified RAP1 # Material, RAP2 # material, RAP3 # The material is mixed with coarse aggregate and fine aggregate according to the designed proportion. In this embodiment, the amount of RAP aggregate in the water-stable mixture is 50%. Specifically, the water-stable mixture is mixed with 20% RAP1 # Material, 20%RAP2 # Material, 10%RAP3 # Aggregate, 32% coarse aggregate, 18% fine aggregate. The gradation range of the mixed crushed stone meets the requirements of Table 2:

[0040]

[0041] Add cement and curing agent to the mixed gravel, the cement content accounts for 4% of the total weight of the high-dosage RAP recycled water-stabilized mixture, and the curing agent content is 8% of the cement content. Cement uses 42.5 grade ordinary Portland cement, and the initial setting time of cement should be no less than 3 hours and the final setting time should be no less than 6 hours.

[0042] In this embodiment, the health-free agent includes an anionic surfactant and a swelling agent, wherein the anionic surfactant includes any one or more of anionic polyacrylamide and fatty alcohol polyoxyethylene ether phosphate, preferably anionic polyacrylamide. The swelling agent includes any one or more of calcium magnesium oxide swelling agents and calcium sulfoaluminate swelling agents, preferably calcium sulfoaluminate swelling agents, such as U-type swelling agents. In the present invention, both the anionic surfactant and the swelling agent are commercially available products.

[0043] The technical indicators of the free health-preserving agent meet the requirements of Table 3 and it should be dissolved in water before adding.

[0044]

[0045] The maximum dry density of the high-dosage RAP regenerated water-stabilized mixture prepared in this example is 2.200 g / cm 3 The water content is 4.0%. The core sample of the high-dosage RAP regenerated water-stabilized mixture prepared in this embodiment, which is 1 day old, is as shown in the attached Figure 1 shown.

[0046] Example 2

[0047] The difference between this embodiment and embodiment 1 is that the amount of RAP in the high-dosage RAP regenerated water-stable mixture is 40%. Specifically, the crushed stone grading in the high-dosage RAP regenerated water-stable mixture is 12% RAP1 # Material, 18%RAP2 # Material, 10%RAP3 # The content and preparation method of other aggregates are the same as those in Example 1.

[0048] Example 3

[0049] The difference between this embodiment and embodiment 1 is that the dosage of the curing agent is 6% of the cement dosage, and the contents of other aggregates and the preparation method are the same as those in embodiment 1.

[0050] Comparative Example 1

[0051] The difference between this comparative example and Example 1 is that the water-stabilized mixture does not contain RAP aggregate and curing agent. Specifically, the water-stabilized mixture in this comparative example includes 33% coarse aggregate, 38% 16-4.75mm fine aggregate, 5% 2.36-4.75mm new aggregate and 24% fine aggregate, the cement content accounts for 4% of the total mass of the water-stabilized mixture, and the moisture content is 4.9%. The preparation method refers to Example 1.

[0052] Comparative Example 2

[0053] The difference between this comparative example and Example 1 is that the content of RAP aggregate in the high-content RAP recycled water-stabilized mixture is 60%. Specifically, the water-stabilized mixture is graded with 30% RAP1 # Material, 20%RAP2 # Material, 10%RAP3 # The amount of cement is 3.5% of the total mass of the high-dosage RAP recycled water-stabilized mixture, and the amount of curing agent is 6% of the cement. The preparation method is the same as that of Example 1.

[0054] Comparative Example 3

[0055] The difference between this comparative example and Example 1 is that the dosage of the curing agent is 10% of the cement dosage, and the contents of other aggregates and the preparation method are the same as those in Example 1.

[0056] Comparative Example 4

[0057] The difference between this comparative example and Example 1 is that the dosage of the curing agent is 4% of the cement dosage, and the contents of other aggregates and the preparation method are the same as those in Example 1.

[0058] Comparative Example 5

[0059] The difference between this comparative example and Example 1 is that RAP1 # Material, RAP2 # material, RAP3 # The coefficient of variation of the material sieve hole passing rate is shown in Table 4:

[0060]

[0061] The coefficient of variation of the recycled old asphalt in RAP in this comparative example is shown in Table 5:

[0062]

[0063] In step 1, the recovered RAP material was not crushed or screened in detail, and the other preparation methods were consistent with those in Example 1.

[0064] Experimental Example 1: Unconfined compressive strength test

[0065] The experimental results are shown in Table 6:

[0066]

[0067] Experimental results analysis:

[0068] The unconfined compressive strength of high-dosage RAP recycled water-stabilized mixtures with different curing agent dosages was improved, mainly because the moisture content of the mixture increased relatively after the curing agent was added, the friction between aggregates decreased, the density increased, and the dispersion of cement was better, which improved the unconfined compressive strength of recycled cement stabilized gravel. However, with the continuous increase in the curing agent dosage, the representative value of the unconfined compressive strength at the same age showed a pattern of first increasing and then decreasing. When the curing agent dosage was 4%, 6%, and 8%, the representative value of the unconfined compressive strength continued to increase with the increase in dosage. When the dosage increased to 10%, the average value of the unconfined compressive strength did not continue to increase, and was lower than the average value of the unconfined compressive strength of 8%. And only when the dosage reached more than 6%, the strength at the age of 1d could reach more than 3.5MPa, meeting the design requirements.

[0069] Comparative Example 1 adopts the preparation method of ordinary water-stabilized mixture. From its test results, it can be seen that the unconfined compressive strength at the age of 1d is 2.2Mpa, which does not achieve the use effect, and its unconfined compressive strength at the age of 7d is also lower than that of the embodiment of the present invention.

[0070] In comparative example 2, the dosage of RAP material was increased, resulting in a decrease in the compressive strength of the prepared water-stabilized mixture, especially at the age of 1 day, which decreased by about 15.6% compared with Example 1. This shows that excessive use of RAP material will cause the compressive strength of the water-stabilized mixture to fail to meet the use standard in the early stage of use.

[0071] Comparative Examples 3 and 4 adjusted the amount of curing agent added. When the curing agent was excessive (10%), the compressive strength of the water-stabilized mixture did not increase but slightly decreased at the age of 1d and 7d. When the curing agent was insufficient, the compressive strength of the water-stabilized mixture decreased significantly at the age of 1d and 7d, and did not meet the use standard.

[0072] RAP1 in Comparative Example 5 # Material, RAP2 # material, RAP3 #The material has not been crushed and screened in detail, and the coefficient of variation of the sieve hole pass rate is large, and the coefficient of variation of the old asphalt has also increased to a certain extent, which has led to a significant decrease in the unconfined compressive strength of the base prepared by the water-stabilized mixture prepared with the RAP material compared to the embodiment of the present invention. The main reason is that due to the increase in the coefficient of variation of the RAP material, it shows that the performance and size uniformity of the RAP material used are poor. The amount of new aggregate and cement added during the design and use process cannot form a good complementary relationship with the RAP material, resulting in a significant decrease in the compressive performance of the prepared water-stabilized mixture.

[0073] Experimental Example 2: Road Performance Test Experiment

[0074] Experimental method: The road performance test items include splitting strength test, compressive rebound modulus test, fatigue resistance test and erosion resistance test. The experimental methods are carried out in accordance with T0806-2009, T0806-2009, T0856-2009 and T0860-2009 standards.

[0075] The experimental results are shown in Table 7:

[0076]

[0077] It can be seen from the above test results that in terms of splitting strength, the water-stabilized mixture prepared in Example 1 of the present invention is greater than the water-stabilized mixture prepared in Comparative Example 5 from the age of 1d to the age of 28d, indicating that the water-stabilized mixture prepared in the present invention has a stronger crack resistance. At the same time, the same is true in the compressive rebound modulus test. The water-stabilized mixture prepared in Example 1 has a greater rebound modulus from the age of 1d to the age of 28d than the water-stabilized mixture prepared in Comparative Example 5, indicating that the water-stabilized mixture prepared in the present invention has a stronger bearing capacity and durability. It can also be intuitively seen in the fatigue resistance test and the scouring mass loss test that the water-stabilized mixture prepared in the present invention has stronger fatigue resistance and stability. In summary, it shows that the present invention performs detailed screening of the RAP material used, and constrains its old asphalt content, size and other indicators through the coefficient of variation, so that the RAP material can be more compatible with the new aggregate and cement after mixing, thereby improving the comprehensive performance of the prepared water-stabilized mixture.

[0078] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive from any point of view. In addition, it should be understood that although this specification is described in accordance with the embodiments, it does not contain only one technical solution. This narrative of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole, and the technical solutions in the embodiments can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. An environmentally friendly high-dosage RAP recycled cement stabilized gravel mixture, characterized by: Includes graded crushed stone, cement and curing agent; The graded crushed stone is composed of the following materials by mass percentage: 12% to 20% RAP1 # Material, 18%~20%RAP2 # Material, 10%RAP3 # Aggregate, 32% to 42% coarse aggregate, 18% fine aggregate; The RAP1 # Particle size is 10mm~20mm, RAP2 # Particle size is 5mm~10mm, RAP3 # The particle size is greater than 0mm and less than 5mm, the coarse aggregate particle size is 16mm to 31.5mm, and the fine aggregate particle size is greater than 0mm and less than 2.36mm; The RAP1 # Material, RAP2 # Materials and RAP3 # The coefficient of variation of the passing rate of the sieve holes below 9.5 mm in the material is 4% to 14%; the coefficient of variation of the passing rate of the sieve holes above 9.5 mm is 2% to 7%; The RAP1 # Material, RAP2 # Materials and RAP3 # The coefficient of variation of the asphalt content of the old material is 4.5% to 5.5%; The coefficient of variation of needle penetration is 6.5% to 7.5%; The coefficient of variation of softening point is 5% to 5.5%; The coefficient of variation of elongation at 10°C is 6% to 9.5%; The cement addition amount accounts for 2.5% to 4% of the total weight of the high-dosage RAP recycled water-stabilized mixture; The amount of the curing agent added is 6% to 8% of the weight of the cement.

2. The environmentally friendly high-dosage RAP recycled cement stabilized gravel mixture according to claim 1, The characteristics are: the moisture content of the high-dosage RAP recycled water-stabilized mixture is 4.0% to 4.5%; the maximum dry density is 2.200g / cm 3 ~2.221 g / cm 3 .

3. According to the environmentally friendly high-dosage RAP recycled cement stabilized gravel mixture described in claim 1, it is characterized by: The curing-free agent includes an anionic surfactant and a swelling agent, wherein the anionic surfactant includes any one or more of anionic polyacrylamide and fatty alcohol polyoxyethylene ether phosphate, and the swelling agent is any one or more of calcium magnesium oxide swelling agents and calcium sulfoaluminate swelling agents; the curing-free agent meets the following technical indicators: pH value is 7-9; alkali content is ≤0.75%; specific surface area is ≥200m2 / kg; initial setting time is ≥3h, final setting time is ≤10h; water reduction rate is ≥25%.

4. The method for preparing an environmentally friendly high-dosage RAP recycled cement stabilized gravel mixture according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1, RAP material recovery and screening: select the old road surface to be milled to obtain the recycled material, crush and screen the recycled material into multiple grades of RAP material, and store it for standby after testing its variability. The milling depth of the old road surface is 30cm-40cm; the milling speed is 10m / min-15m / min; Step 2: Mixing the mixture: Mix the qualified RAP material with coarse aggregate and fine aggregate to obtain a mixture. After the mixture is screened and tested to have a qualified gradation range, cement and curing agent are added to the mixture in sequence, and stirred and mixed to form a high-dosage RAP recycled water-stabilized mixture; the gradation range of the mixture meets the following requirements: 。 5. The method for preparing an environmentally friendly high-dosage RAP recycled cement stabilized gravel mixture according to claim 4, characterized in that: In the step 2, the health-preserving agent is pre-dissolved in water.

Citation Information

Patent Citations

  • RAP high-doping-amount regenerated mixture as well as preparation method and application of RAP high-doping-amount regenerated mixture

    CN113698138A

  • Preparation methods of cold recycled asphalt mixtures, cold recycled asphalt mixtures and their applications

    CN116693242B

  • Full-flexible hot mix plant recycled asphalt pavement structure

    CN112832087A

  • Preparation method of rapidly-formed recycled water-stable base layer

    CN116623487A